Serum and follicular fluid levels of serotonin, kisspeptin, and brain-derived neurotrophic factor in patients undergoing in vitro fertilization: an observational study: Neurohormones in patients receiving IVF. Issue 4 (October 2020) - Bódis, József; Sulyok, Endre; Kőszegi, Tamás; Prémusz, Viktória; Várnagy, Ákos; Koppán, Miklós
Objective: This study aimed to examine the effect of interactions between serotonin (5-HT), brain-derived neurotrophic factor (BDNF), and kisspeptin on the reproductive potential in women receiving in vitro fertilization (IVF). Methods: Paired serum and follicular fluid (FF) samples were obtained from 30 consecutive patients receiving IVF. Primary and secondary outcome measures were the rate of chemical/clinical pregnancy and the number of mature oocytes and embryos, respectively. Serum and FF 5-HT, BDNF, kisspeptin, and platelet-activating factor (PAF) levels were measured by enzyme-linked immunosorbent assay. Results: In response to ovarian hyperstimulation, serum 5-HT and kisspeptin levels significantly increased, whereas serum BDNF and PAF levels remained unchanged. These factors were detected in FF, but they were unrelated to serum levels. FF 5-HT and BDNF levels were positively correlated. Serum kisspeptin levels were negatively correlated with FF BDNF and serum and FF PAF levels. Women who were pregnant had significantly lower FF BDNF levels compared with women who were not pregnant (21.96±12.75 vs 47.63±52.90 µg/mL). Multivariate stepwise linear regression and logistic regression analyses showed that only 5-HT and kisspeptin improved IVF outcome. Conclusions: This study indicates a role of serotoninergic mechanisms in success of IVF, but the contribution of interacting neuropeptides requires additional investigation.